A Cross-sectional Investigation of the Relationship between Corporate Governance and Financial Performance in Nepalese Commercial Banks - G.C., Prakash (Devkota Journal of Interdisciplinary Studies, 2024)
The study aims to investigate how commercial banks' financial performance in Nepal relates to corporate governance policies. The study uses a cross-sectional survey comprising 317 commercial bank stakeholders – employees, shareholders, and consumers among others. Field surveys helped to compile the data. Descriptive statistics and correlation analysis have helped to examine the acquired data. The results show that although commercial banks' corporate governance policies are sufficient, they could need improvement. Advancement of ideal board composition and structure, enhancement of disclosure and transparency, and protection of shareholder interests should take the front stage. Good financial performance corresponds favourably with the application of efficient governance policies. The study results have several consequences for legislators and authorities aiming to enhance the commercial banks' governance in Nepal.